Bioelectricity production from kitchen wastewater using microbial fuel cell with photosynthetic algal cathode. (January 2020) - Naina Mohamed, Samsudeen; Ajit Hiraman, Pohekar; Muthukumar, K.; Jayabalan, Tamilmani
Graphical abstract: Highlights: MFC performance was investigated using kitchen wastewater as a substrate. Synechococcus sp. and Chlorococcum sp. cultured in BG11 medium acted as catholyte. MFC achieved higher power density in Synechococcus sp. than Chlorococcum sp. Biomass growth and current density increased by sparging of generated CO2 from anode. Wastewater COD concentration, light intensity significantly improved the power production. Abstract: In this study, the treatment of kitchen wastewater was demonstrated using microbial fuel cell (MFC) consisting photosynthetic microorganism as cathode catalyst. The power density and biomass generation were investigated using two photosynthetic microorganisms namely Synechococcus sp. and Chlorococcum sp., respectively. Cyclic Voltammogram analysis was performed to study the exoelectrogenic activity of mixed culture microorganisms present in the wastewater. The MFC experimental results showed that both species influenced the power production and COD removal efficiency. The MFC observed the higher power density of 41.5 ± 1.2 mW/m 2 with Synechococcus sp. as compared to Chlorococcum sp. (30.2 ± 0.8 mW/m 2 ). The effect of CO2 supply, light intensity and wastewater COD concentration on MFC performance were investigated. This study demonstrated the possibility of bioelectricity generation, CO2 sequestration and biomass production with the algae biocatholyte during the treatment of kitchen wastewater in the MFC.